Determination of volume–time curves for the right ventricle and its outflow tract for functional analyses. Issue 6 (4th February 2013) - Gabbert, Dominik D.; Entenmann, Andreas; Jerosch‐Herold, Michael; Frettlöh, Felicitas; Hart, Christopher; Voges, Inga; Pham, Minh; Andrade, Ana; Pardun, Eileen; Wegner, P.; Hansen, Traudel; Kramer, Hans‐Heiner; et al.
<x xml:space="preserve">Abstract</x> Purpose The determination of right ventricular volumes and function is of increasing interest for the postoperative care of patients with congenital heart defects. The presentation of volumetry data in terms of volume‐time curves allows a comprehensive functional assessment. By using manual contour tracing, the generation of volume–time curves is exceedingly time‐consuming. Methods This study describes a fast and precise method for determining volume–time curves for the right ventricle and for the right ventricular outflow tract. The method applies contour detection and includes a feature for identifying the right ventricular outflow tract volume. The segregation of the outflow tract is performed by four‐dimensional curved smooth boundary surfaces defined by prespecified anatomical landmarks. Results The comparison with manual contour tracing demonstrates that the method is accurate and improves the precision of the measurement. Compared to manual contour tracing the bias is <0.1% ± 4.1% (right ventricle) and −2.6% ± 20.0% (right ventricular outflow tract). The standard deviations of inter‐ and intraobserver variabilities for determining the volume of the right ventricular outflow tract are reduced to less than half the values of manual contour tracing. The time consumption per patient is reduced from 341 ± 80 min (right ventricle) and 56 ± 11 min (right ventricular outflow tract) using manual contour tracing to 46 ± 9 min for a combined analysis of right ventricle and right ventricular outflow tract. Conclusion The analysis of volume–time curves for the right ventricle and its outflow tract discloses new evaluation methods in clinical routine and science. Magn Reson Med 70:1718–1727, 2013. © 2013 Wiley Periodicals, Inc.